A Design Approach to Evaluate the Load-Carrying Capacity of Reinforced Concrete Slabs Considering Tensile Membrane Action. Issue 2 (3rd April 2021) - Colombo, Matteo; Martinelli, Paolo; di Prisco, Marco
Abstract: This paper proposes a novel simplified analytical approach, named the slab strip model, to assess the ultimate bearing capacity of reinforced concrete (RC) two-way slabs when large deflections are reached and tensile membrane action plays a key role. The motivation for the work derives from the fact that in recent years, investigations into the behaviour and modelling of laterally restrained and unrestrained RC slabs have been intensified owing to the reserve of bearing capacity provided by the tensile membrane action. The approach has been developed in the framework of the strip method and analyses the tensile membrane effect. Two failure criteria are accounted for: the maximum ultimate slab strip elongation and the maximum ultimate rotation of the structure at the supports. The rationality of the proposed approach is validated for laterally restrained slab strips and two-way laterally unrestrained simply supported slabs by comparing the analytical results with experimental data from the literature. The results show that despite its simplicity the method is accurate in estimating the load-carrying capacity of RC two-way slabs able to develop significant tensile membrane action. For its characteristics, the proposed method can be considered a useful initial design tool in a robustness context for conducting alternative load path analysis of RC structures characterised by two-way slabs.